PENGARUH KUALITAS PELAYANAN TERHADAP MINAT KONSUMEN MENGGUNAKAN JASA PT. ALMUNA TOUR AND TRAVEL BUGIH PAMEKASAN - Rahayu, Runik Puji; Alfian, Nurul (JURNAL AKUNTANSI DAN INVESTASI, 2018)
The purpose of this study is to find out whether service quality has an effect on simultaneous consumer interest using the services of PT. Almuna Tour and Bugih Pamekasan Travel and to find out which variable is the most dominant influence on consumer interest using the services of PT. Almuna Bugih Pamekasan Tour and Travel. the independent variables used are reability (X1), Responsiveness (X2), Assurance (X3), consumer interest (Y). Based on the results of calculations carried out by researchers, the influence of service quality on consumer interest uses Pt services. Almuna Tour and Bugih Pamekasan Travel, reliability, responsiveness and assurance. simultaneously the effect can be said truthfully, this is evidenced by the results of the calculation of SPSS with a real level of 5% or with a 95% confidence level obtained Fcount 19.759 while Ftable of 2.74. Because in this study service quality affects consumer interest in using travel services.